Implementing outside the box: Community-based social service provider experiences with using an alcohol screening and intervention - Patterson Silver Wolf (Adelv unegv Waya), David A. (J Soc Serv Res, 2015)
OBJECTIVE: The aim of this study is better understand perceptions of front-line social service workers who are not addiction specialists, but have to address addiction-related issues during their standard services. METHOD: Six social service organizations implemented a validated alcohol assessment and brief education intervention. After a 3-month trial implementation period, a convenience sample of 64 front-line providers participated in six focus groups to examine barriers and facilitators to the implementation of an alcohol screening and brief intervention. RESULTS: Three themes emerged: (1) usefulness of the intervention, (2) intervention being an appropriate fit with the agency and client population, and (3) worker commitment and proper utilization during the implementation process. CONCLUSIONS: A cross-cutting theme that emerged was the context in which the intervention was implemented, as this was central to each of the three primary themes identified from the focus groups (i.e., the usefulness and appropriateness of the intervention and the implementation process overall). Practitioner buy-in concerns also indicate the need for better addiction service training opportunities for those without addiction-specific educational backgrounds. Future research should assess whether targeted trainings increase addiction screening and education in social services settings.